Effectiveness of Hybrid Learning Using Streaming Technology in Education - Wahyudin, Aji; Nashirudin, Humam; Furqon, M.; Rohmad, Rohmad; Choironi, M. Afif (Universitas Nurul Jadid Probolinggo, Indonesia, 2023)
This study aims to evaluate the effectiveness of hybrid learning at Madrasah Aliyah Negeri 4 Kediri, focusing on instructional design and the quality of streaming technology. The research method employed is qualitative with a case study approach to explore the experiences of students and faculty regarding hybrid learning. The subjects of the study include 20 students and 10 faculty members involved in the hybrid learning program at the university. Data collection techniques included semi-structured interviews and participatory observations. The collected data were analyzed using thematic analysis to identify patterns and key themes related to the impact of instructional design and technical issues on student engagement. The results indicate that interactive instructional design contributes to increased student engagement, while technical problems such as buffering and poor video quality significantly hinder the effectiveness of learning. These findings underscore the importance of integrating high-quality streaming technology with effective instructional design to enhance the learning experience in hybrid education.